2016
DOI: 10.1371/journal.pone.0162453
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Upfront Stereotactic Ablative Radiotherapy Combined with Image-Guided, Intensity Modulated Radiotherapy (IG-IMRT) or IG-IMRT Alone for Locally Advanced Non-Small Cell Lung Cancer

Abstract: BackgroundImage-guided (IG) intensity-modulated radiotherapy (IMRT) enables maximal tumor margin reduction for the sparing of organs at risk (OARs) when used to treat locally advanced non-small cell lung cancer (NSCLC) with definitive chemo-radiation. It also allows for the incorporation of stereotactic ablative radiotherapy (SABR) into the treatment regimen. Here, we describe our initial experience in combining definitive upfront SABR to the primary lesion with chemo-radiation delivered with conventionally fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…If the high radiation doses would be focused only on the exact location of the primary tumor using intensity-modulated or stereotactic ablative radiotherapy (SABR) with image guidance, the extra dosing to organs at risk, such as the heart or mediastinum, could be minimized. For example, Alexander et al have reported the feasibility of definitive image-guided intensity modulated radiotherapy (IMRT) combined with SABR in LA-NSCLC patients to increase the dose to the primary tumor (18). In their report, 40-50 Gy in 4 fractions of SABR were delivered to the primary tumor and 63 Gy in 35 fractions of IMRT were delivered to lymph node target volume.…”
Section: Discussionmentioning
confidence: 99%
“…If the high radiation doses would be focused only on the exact location of the primary tumor using intensity-modulated or stereotactic ablative radiotherapy (SABR) with image guidance, the extra dosing to organs at risk, such as the heart or mediastinum, could be minimized. For example, Alexander et al have reported the feasibility of definitive image-guided intensity modulated radiotherapy (IMRT) combined with SABR in LA-NSCLC patients to increase the dose to the primary tumor (18). In their report, 40-50 Gy in 4 fractions of SABR were delivered to the primary tumor and 63 Gy in 35 fractions of IMRT were delivered to lymph node target volume.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two retrospective studies reported an inverted sequence associating 4-fraction primary tumor SBRT followed by nodal NFRT. In 3 patients of their larger NSCLC cohort, Chi et al observed neither local failure or death at 2 years, nor G≥3 AE [22]. In patients with small, isolated lesion (GTV, median 6.4cc) distant from the nodal involvement, Kim et al…”
Section: Sequential Tumor Sbrt and Nodal Nfrtmentioning
confidence: 95%
“…All titles and abstracts were retrieved and screened. Among the 28 records selected for full-text eligibility assessment, 18 met inclusion criteria [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). The characteristics of included studies are summarized in Table 1.…”
Section: Identified Studies and Quality Assessmentmentioning
confidence: 99%